Listening errors at chunk level in the case of Vietnamese University learners of English as a foreign language - Luu, Vy Thi Mai; Trinh, Thuy Thanh (Penerbit Universiti Kebangsaan Malaysia, 2023)
Research has shown that error analysis (EA) can be a valuable tool for linguistic scholars to collect useful information on second language (L2) acquisition. In the domain of L2 listening development, identifying patterns of learners’ erroneous output allows both teachers and students to have an overview of learners’ listening problems. On this premise, remedial actions can be taken for the achievement of effective listening comprehension. Having said that, the goal of this study is to investigate the common types of listening errors made by 12 EFL university students at a private university in Vietnam. Specifically, the study attempts to seek an understanding of how listeners process speech at chunk level and how their listening transcriptions reflect their listening processes. Sixty chunks extracted as a separate clip from 15 dialogues with basic features of the oral language were embedded in listening tasks on a selfaccess online platform. Error analysis of a total of 720 transcriptions reveals that chunks containing errors occupied 44 percent, suggesting that at the chunk level, students still struggled to construct the meanings of the aural input. Major listening errors identified are related to sound misperception, including confusion, omission, addition, and misformation. The findings of this study stress the significance of respecting learners’ meaning-making mechanisms in the listening process by giving listeners more control in accessing listening materials. On top of that, it highlights the priority of listening at the chunk level without contextual clues at the earlier stages of listening, which can be a head start for their listening development. More implications for language teachers and researchers in listening are also discussed.